The rare case report of interstitial lung disease with normal serum level of IgG4 developed six years after treatment of autoimmune pancreatitis - Adzic-Vukicevic, Tatjana; Stojsic, Jelena; Barac, Aleksandra; Blanka-Protic, Ana; Andrejevic, Sladjana; Raljevic, Snezana (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Not available